A discussion of new business models for 3D printing. (25th September 2007) - Anderson, Phil; Sherman, Cherie Ann
3D printing, which is just now becoming affordable to small businesses and potentially to the individual consumer, can convert digital files to tangible products in only a few hours. This technology, which would enable digital files representing a physical product to be sent via the internet and fabricated at the time and place chosen by the consumer, has the potential to disrupt existing business models for product distribution. In addition, this technology also has the potential to generate a variety of new business models, which would enhance the average consumer's lifestyle. Applications of 3D printing could revolutionise internet sales and marketing strategies, at every stage of product marketing. This paper discusses the technology and its potential for use with the internet, attempting to identify new business models with value for future marketing research.